CURRENT STATE OF WORKING AND HEALTH CONDITIONS OF HEALTH WORKERS OF DENTAL SPECIALITY - T. Yu. Bykovskaya; E. Yu. Leontyeva; A. S. Ivanov (Кубанский научный медицинский вестник)
Aim. To conduct a review of literature concerning current state of working and health conditions of health workers of dental speciality.Materials and methods. To conduct a review of Russian and foreign literature of recent years from RSCI, Scopus, Web of Science, Pubmed.Results. Dental speciality is considered to be one of the largest medical specializations. Development and implementation of innovative technologies, expansion of apparatus and medicamental treatment methods in dentistry increased the amount of harmful factors in the workplace of the specialists of this sphere.Conclusion. Hygienic working conditions assessment and dental specialists’ workflow organization data require significant addition and personal professional risk assessment. The expansion of specification of the influence aspects of occupational hazards in the dentistry sphere will make it possible to decrease the risk of pathological processes emergence in the specialists of this sphere.